PEMBERIAN GANTI RUGI ATAS TANAH SISA AKIBAT PENGADAAN TANAH UNTUK KEPENTINGAN JALAN TOL KUNCIRAN SERPONG (STUDI KASUS: PUTUSAN MAHKAMAH AGUNG NOMOR 3049K/PDT/2018) - Yolanda Limarta; Hanafi Tanawijaya (Fakultas Hukum Universitas Tarumanagara, 2020)
Basic Agrarian Principles Number 5 of 1960 concerning Basic Agrarian Principles Article 1 paragraph 1 states that all land within the territory of the Indonesian State is the common land of all Indonesian people. Article 6 of the Basic Agrarian Law which states that all land rights have a social function. Land acquisition is carried out solely for the sake of public interest which aims to prosper the people. However, in the Supreme Court Decision Number 3049K / Pdt / 2018, the Judge decided that there was no compensation for the remaining land from the applicant, while the remaining land had been regulated in Article 35 of Law Number 2 of 2012. The research method used was normative research, which aims to know the procedures for land acquisition and assessment of compensation for the remaining land. As well as providing advice to the Appraisal so that they can carry out a careful and professional assessment so as not to cause harm to the land owner.